2013
DOI: 10.1016/j.jedc.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Government education expenditures in early and late childhood

Abstract: Human capital investment in early childhood can lead to large and persistent gains. Beyond this window of opportunity, human capital accumulation is more costly. Despite compelling evidence in support of this notion, government education spending is allocated disproportionately toward late childhood and young adulthood. We consider the consequences of a reallocation using an overlapping generations model with private and public spending on early and late childhood education. Taking as given the higher returns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…This author uses a dynamic equilibrium model (Lloyd-Ellis, 2000) which explores the involvement of education spending over successive generations of individual and finds that there is low allocations for basic education and the base and higher human capital affects, with opposite signs, global equality and efficiency; results also obtained by Welsch (2008). From an overlapping generation's model, Blankenau and Abington (2013) show that spending on human capital in early childhood generates significant gains for the community. Arcalean and Schiopu (2008) study, for their part, the interaction between public and private spending in a two-stage education framework and their impact on economic growth.…”
Section: Economic Effects Of the Distribution Of Public Spending Of Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…This author uses a dynamic equilibrium model (Lloyd-Ellis, 2000) which explores the involvement of education spending over successive generations of individual and finds that there is low allocations for basic education and the base and higher human capital affects, with opposite signs, global equality and efficiency; results also obtained by Welsch (2008). From an overlapping generation's model, Blankenau and Abington (2013) show that spending on human capital in early childhood generates significant gains for the community. Arcalean and Schiopu (2008) study, for their part, the interaction between public and private spending in a two-stage education framework and their impact on economic growth.…”
Section: Economic Effects Of the Distribution Of Public Spending Of Educationmentioning
confidence: 99%
“…A recent economic literature has focused on the distribution of human capital investment to support sustainable economic growth [Driskill and al (2007), Blankenau and Abington (2013), Su (2004), Arcalean and Schiopu (2008), Ben Mimoun (2007)…]. This literature demonstrates explicitly that excessive emphasis placed by several countries in Latin America or sub-Saharan Africa on higher education to the detriment of primary and secondary education could strengthen the adverse effects of high inequality and the financial constraint on investment in post-primary teaching in these countries.…”
Section: Introductionmentioning
confidence: 99%
“…Next, unlike many previous studies, he found a positive and significant effect of secondary educational spending deflated using the traditional GDP deflator on both PISA math scores and literacy scores (both significant at the one percent level). Abington and Blankenau (2013) considered the consequences of a reallocation using an overlapping generations' model -with private and public spending on early and late childhood education. By the assumption that the early childhood investment has higher return, their survey showed that the current allocation may nonetheless be appropriate.…”
Section: Theoretical Principles and Literature Reviewmentioning
confidence: 99%
“…These costs can be either direct (for example, a direct cost per education hour) or indirect like property or wealth taxes that are earmarked for the provision of public education (see below). 8 This specification is a hybrid between education time and inherited wealth. By choosing appropriate parameter values we can shift the tax base to reflect di↵erent policy regimes.…”
Section: User Fees Functionmentioning
confidence: 99%